INTERNATIONAL AND EUROPEAN LEGAL FRAMEWORK ON DISCRIMINATION BASED ON SEX AND GENDER - Jovevski, Lazar; Cestojnova, Pepica (Harmonius - Journal of Legal and Social in Studies in South East Europe, 2020)
In this scientific paper, the authors have described the international and European legal framework on discrimination based on sex and gender. The legal regulation on protection from discrimination is analysed from several angles. The authors give special consideration to positive legal sources analysis, with an emphasis on constitutional provisions, from the international perspective, considering the scope of this paper. The paper tries to examine the endeavours of the International Labour Organization to provide equal opportunities for the employment and promotion of the employees, to prevent activities leading to unequal treatment and to eliminate discrimination through legislative activity and politics. The authors have considered certain Conventions of International Labour Organization, which are referring to protection from discrimination based on sex and gender. In addition, the EU legislative acts regarding this topic are reviewed, through the analysis of the EU’s antidiscrimination law on equal treatment of men and women, among which we accentuate Directive 76/207 from 1976 on the implementation of the principle of equal treatment for men and women as regards access to employment, vocational training and promotion, and working conditions.
Keywords: Equality. – Gender. – Sex. – Discrimination. – Working conditions